The Role of Economic Seminars in Promoting Digital Transformation of UMKM in Kalumpang Village - Febrian Krisnawati (SATRIA BHAKTI, 2026)
Kuliah Kerja Mahasiswa (KKM) aims to enhance the digital literacy of Usaha Mikro, Kecil, dan Menengah (UMKM) in Kalumpang Village through an economic seminar titled “Introduction to Digital Systems.” A total of 25 UMKM participants attended the training, which covered topics including the concept of the digital economy, online marketing, application-based financial management, and branding strategies. The methods employed consisted of interactive lectures, demonstrations, and question-and-answer sessions. The evaluation results indicated a significant increase in participants’ understanding of digital technology, with 80% successfully creating business social media accounts and 70% able to produce simple promotional content. The activity also identified challenges such as limited internet connectivity and participants’ minimal technical experience. This training is expected to serve as an initial step in strengthening the competitiveness of local UMKM, with recommended follow-up actions including continuous mentoring and improvements to digital infrastructure.